2022
DOI: 10.5812/compreped.117569
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effect of Bowel Management Training Program on Quality of Life in Children with Fecal Incontinence

Abstract: Background: The bowel management program (BMP) promotes independence and self-sufficiency in children, helping them to integrate into the community. It also enhances their sense of well-being and provides them with a high-quality life. Objectives: This study aimed to determine the effect of BMP on quality of life (QOL) in children with fecal incontinence in Mofid Children’s Hospital in Tehran, Iran from 1 February, 2019 to 1 February, 2020. Methods: The target population of this clinical trial was all individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…A pilot study on children with FI who fail traditional outpatient treatment showed that group therapy (including sessions about the gastrointestinal system, medications, toilet sitting posture, hydration fiber, and behavior contracts) could improve the results (30). Also, another study in Iran revealed that a bowel management training program could be effective for treating FI and improving the quality of life in children (31).…”
Section: Discussionmentioning
confidence: 99%
“…A pilot study on children with FI who fail traditional outpatient treatment showed that group therapy (including sessions about the gastrointestinal system, medications, toilet sitting posture, hydration fiber, and behavior contracts) could improve the results (30). Also, another study in Iran revealed that a bowel management training program could be effective for treating FI and improving the quality of life in children (31).…”
Section: Discussionmentioning
confidence: 99%